Hybrid-duplex based control and non-payload communication systems for UAVs : an outage analysis - Tan, Ernest Zheng Hui (2020)
In this paper, a hybrid-duplex control and non-payload communication (HBD-CNPC) system is proposed to address spectrum scarcity in unmanned aerial vehicle (UAV) communications. By considering the effects of fading and inter-UAV interference, an outage analysis of the proposed system is conducted. It is shown that the successive interference cancellation (SIC) detector achieves lower outage probability than the interference ignorant (II) detector when the desired signal experiences more severe fading than the interfering signal. It is also demonstrated that the HBD-CNPC system achieves better reliability with longer transmission rage and lower transmission requirements over half-duplex (HD) CNPC systems.